Design of a Performance Measurement Framework for the Sudanese Construction Contractor’s Organizations (University of Khartoum Engineering Journal, 2022)
This paper investigates the relations between the Sudanese construction contractor’s and other relatedinstitutions “resources” in term of project management capabilities, strategic decisions, strength of relationshipswith other parties and external factors, construction project performance and contractor’s organization performancefrom a resource based perspective. A structural equation (SEM) model was set to measure the seven latent variablesthrough their constituent variables. Based on the findings of this study, it can be concluded that, the paperintroduced a new method to measure performance in both qualitative and the quantitative terms.